CONSEQUENCES OF INTERMITTENT FASTING FOR NEUROPLASTICITY: : AN INTEGRATIVE REVIEW - Henrique Leite Guedes, Idrys; Luisa de Souza Holanda, Anna; Vieira da Silveira Santos, Daniela; Romaneto Marques, Grazielle; Carlos de Oliveira Dutra, João; Franco De Almeida, Leonardo (Health and Society, 2021)
Neuroplasticity occurs from human development until the end of senility and, despite the dependence on food, the regulation of the diet on neurons and nerve synapses is not restricted to the availability of nutrients. In turn, intermittent fasting, as a dietary strategy, represents not only a modern technique for weight loss, but also an important historical factor for the occurrence of persistent organic adaptations. Based on this interrelation, evidence was collected from databases that associated, positively or negatively, neuroplasticity with intermittent fasting in humans. From the review of the selected articles, the various ways in which intermittent fasting affects neuroplasticity, influencing energy metabolism, triggering signaling pathways, modulating components of the immune system and altering cellular components were identified. All of these changes create a favorable environment for the emergence and maintenance of neurons, as well as for the formation of new nerve synapses.